Cultural Responsive Teaching: Increasing Student PPKn Learning Outcomes - Latipia Damayanti; Cecil Hiltrimartin; Destiana Wati (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research will explore how a culturally responsive teaching approach can improve students' cognitive learning outcomes. This classroom action research aims to enhance students' cognitive learning outcomes using a culturally responsive teaching approach. Methodology: This research was carried out in class III in Civics subjects. The type of research method used by researchers was Classroom Action Research. The population and sample used in this study were all class III students at Elementary School 07 Palembang. Data collection techniques used by researchers are observation, field notes, and tests. Data analysis techniques used are qualitative analysis and quantitative analysis. Main Findings: The results of this research are that the application of the culturally responsive teaching approach to Civics subjects in class III can improve student learning outcomes with results in cycle I as much as 57.6%, cycle II as much as 73%, and cycle III as much as 88.4% and post-test 92%. .3% with a student completion target of 85%. Novelty/Originality of this study: Researchers used a culturally responsive teaching approach to improve students' cognitive learning outcomes in grade III Elementary School Civics subjects.